Tourism value of historical, archaeological and religious bases in Hawramabad using GIS - مارف, شەماڵ علی; Mustafa, Rebaz Luqman (Sulaimani Journal for Humanities, 2019)
The touristic activity is fully integrated with the remains of human life and civilization. The sacred archaeological and religious areas are raw material for the human elements embodied in any tourist area, which can attract the attention of many tourists to it. It is possible to say that the areas rich in archaeological and religious sources give way to the human being to take the full experience and qualification of the past of other peoples and to enjoy their knowledge and how to deal with them and their stark views, as well as their experience of how they live and their growing situation, in addition to their knowledge of their architectural and engineering past of ancient and ancient peoples; So many tourists want to visit those areas, which also have an archaeological and religious view. The study area of Hawraman includes historical, cultural and religious foundations that attract the attention of tourists. It also becomes an essential factor to attract the attention of a large number of tourists annually. The most important tourist areas are: Zellum Castle, Khurmal Grand Mosque, Etc.); the Government and the relevant authorities should therefore strictly promote the development of religious and cultural tourism as well as other types of ecotourism so that the region remains a center of tourism integration.